Entropic Multi-Relaxation-Time Lattice Boltzmann Model for Large Density Ratio Two-Phase Flows (Communications in Computational Physics, 2023)
We propose a multiple relaxation time entropic realization of a recent two-phase flow lattice Boltzmann model [S.A. Hosseini, B. Dorschner, and I. V. Karlin,Journal of Fluid Mechanics 953 (2022)]. While the original model with a single relaxation time allows us to reach large density ratios, it is limited in terms of stabilitywith respect to non-dimensional viscosity and velocity. Here we show that the entropicmultiple relaxation time model extends the stability limits of the model significantly,which allows us to reach larger Reynolds numbers for a given grid resolution. Thethermodynamic properties of the solver, using the Peng–Robinson equation of state,are studied first using simple configurations. Co-existence densities and temperaturescaling of both the interface thickness and the surface tension are shown to agree wellwith theory. The model is then used to simulate the impact of a drop onto a thin liquidfilm with density and viscosity ratios matching those of water and air both in two andthree dimensions. The results are in very good agreement with theoretically predictedscaling laws and experimental data.视频.mp4